2021
DOI: 10.3390/molecules26133973
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity and Apoptosis Induction of Gold(III) Complexes Containing 2,2′-Bipyridine-3,3′-dicarboxylic Acid and Dithiocarbamates

Abstract: Three novel gold(III) complexes (1–3) of general composition [Au(Bipydc)(S2CNR2)]Cl2 (Bipydc = 2,2′-bipyridine-3,3′-dicarboxylic acid and R = methyl for dimethyldithiocarbamate (DMDTC), ethyl for diethyldithiocarbamate (DEDTC), and benzyl for dibenzyldithiocarbamate (DBDTC)) have been synthesized and characterized by elemental analysis, FTIR and NMR spectroscopic techniques. The spectral results confirmed the presence of both the Bipydc and dithiocarbamate ligands in the complexes. The in vitro cytotoxic studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The best complex 333 , which contained ethyl for diethyldithiocarbamate (DEDTC) in the MCF-7 cell line, reached 2.7 ± 0.1 μM, and further studies showed that complex 333 induced cell death through apoptosis. 239 Babak et al designed a range of new gold( iii ) complexes, and activated and released metformin prodrug by adjusting the cyclometalated gold( iii ) complex. The cytotoxicity of complex 334 was the most effective among them.…”
Section: Gold(iii) Complexes As Anticancer Agentsmentioning
confidence: 99%
“…The best complex 333 , which contained ethyl for diethyldithiocarbamate (DEDTC) in the MCF-7 cell line, reached 2.7 ± 0.1 μM, and further studies showed that complex 333 induced cell death through apoptosis. 239 Babak et al designed a range of new gold( iii ) complexes, and activated and released metformin prodrug by adjusting the cyclometalated gold( iii ) complex. The cytotoxicity of complex 334 was the most effective among them.…”
Section: Gold(iii) Complexes As Anticancer Agentsmentioning
confidence: 99%
“…Furthermore, dithiocarbamates have the potential to activate key proteins involved in cellular mechanisms such as apoptosis, oxidative stress, transcription, and degradation, which now has sparked interest in these molecules as chemotherapeutic agents. 71,171,174,200 As mentioned above, studies on cancer cells have indicated that cancerous cells are far more susceptible to proteosome suppression than normal cells. 201–205 This opens opportunities to design compounds which preferentially bind to proteasomes.…”
Section: Dithiocarbamate Complexes In Cancer Therapymentioning
confidence: 98%
“…Furthermore, due to the interaction of an extra S-donor moiety such as cysteine, methionine, and other amino acids with S-groups, square planar complexes from dithiocarbamate ligands could result to even more stable complexes. [174][175][176] As a result, further complexation of the central metal with protein molecules containing the thiol moiety which is likely to cause severe side effects, such as liver toxicity (hepatotoxicity) and kidney toxicity (nephrotoxicity) are prevented. [177][178][179][180] Metal complexes from dithiocarbamate nanoparticles and polymeric materials are increasingly being explored as therapeutic strategies.…”
Section: Perspective Dalton Transactionsmentioning
confidence: 99%
“…Several cyclometalated Au­(III) complexes have been shown to induce significant antiproliferative activity by apoptosis or autophagy. We expected that Au-1 – Au-5 recapitulate these features. Au-1 – Au-5 showed lower IC 50 values compared to cisplatin (a first-line chemotherapeutic drug) in the panel of cancer cells studied: MDA-MB-468 and MDA-MB-231 (human breast cancer), 4T1 (murine breast cancer), and BT333 (human glioblastoma) 72 h post-treatment by MTT (Table , Figures S60–S65).…”
Section: Resultsmentioning
confidence: 99%